Pengembangan Modul Bimbingan dan Konseling untuk Pencegahan Penyalahgunaan Narkoba di Sekolah - Rani Mega Putri; Neviyarni S.; Daharnis Daharnis (Jurnal Konseling dan Pendidikan, 2013)
The problem of drug abuse has penetrated up to the world of education, including SMP. Many ways that could be used by guidance and counseling teachers or counselors to enhance students' understanding of the dangers of drug abuse, one of them by using the media as an exciting learning modules. Module was one of tools that addresses learning about a subject systematically arranged and sequentially to facilitate students achieve and master a targeted competencies along with guidelines for the use of teachers. This study aimed: (1) to formulate guidance and counseling module for drug abuse prevention in school-appropriate content to be used by guidance and counseling teacher or counselor, and (2) to describe the level of applicability formulation guidance and counseling module for drug abuse prevention in school by guidance and counseling teacher or counselor. This research was conducted using development research methods, with guided model development step ADDIE (Analyze, Design, Development, Implementation, and Evaluation). The subjects of the trial research were (1) the content expert, and (2) the target users of the product, was guidance and counseling teacher or counselor, who was taken by using purposive sampling method, in order to obtain test subjects research, namely 3 content experts, and 3 people guidance and counseling teacher or counselor. This study was conducted with a limited research product tested and the data was analyzed descriptively. The results of the research showed that: (1) guidance and counseling module to prevent drug abuse, as a content was very feasible for used by students and guidance and counseling teachers or counselors in implementation of service, (2) the level of guidance module and counseling applicability to prevent of drug abuse rated very high for used by students. Based on these results of the research, generally, it could be concluded that the research products produced were feasible and could be used to help students in the context of prevention of drug abuse in schools. Finally the research product was highly recommended to be introduced and used by guidance and counseling teacher or counselor at school in SMP.